Change in full immunization inequalities in Indian children 12-23 months: an analysis of household survey data - Brian Wahl; Madhu Gupta; Daniel J. Erchick; Bryan N. Patenaude; Taylor A. Holroyd; Molly Sauer; Madeleine Blunt; Mathuram Santosham; Rupali Jayant Limaye (BMC, 2021)
Abstract Background India has made substantial progress in improving child health in recent years. However, the country continues to account for a large number of vaccine preventable child deaths. We estimated wealth-related full immunization inequalities in India. We also calculated the degree to which predisposing, reinforcing, and enabling factors contribute to these inequalities. Methods We used data from the two rounds of a large nationally representative survey done in all states in India in 2005-06 (n = 9582) and 2015-16 (n = 49,284). Full immunization status was defined as three doses of diphtheria-tetanus-pertussis vaccine, three doses of polio vaccine, one dose of Bacillus Calmette-Guérin vaccine, and one dose of measles vaccine in children 12-23 months. We compared full immunization coverage by wealth quintiles using descriptive statistics. We calculated concentration indices for full immunization coverage at the national and state levels. Using predisposing, reinforcing, and enabling factors associated with full immunization status identified from the literature, we applied a generalized linear model (GLM) framework with a binomial distribution and an identity link to decompose the concentration index. Results National full immunization coverage increased from 43.65% in 2005-06 to 62.46% in 2015-16. Overall, full immunization coverage in both 2005-06 and 2015-16 in all states was lowest in children from poorer households and improved with increasing socioeconomic status. The national concentration index decreased from 0.36 to 0.13 between the two study periods, indicating a reduction in poor-rich inequality. Similar reductions were observed for most states, except in states where inequalities were already minimal (i.e., Tamil Nadu) and in some northeastern states (i.e., Meghalaya and Manipur). In 2005-06, the contributors to wealth-related full immunization inequality were antenatal care, maternal education, and socioeconomic status. The same factors contributed to full immunization inequality in 2015-16 in addition to difficulty reaching a health facility. Conclusions Immunization coverage and wealth-related equality have improved nationally and in most states over the last decade in India. Targeted, context-specific interventions could help address overall wealth-related full immunization inequalities. Intensified government efforts could help in this regard, particularly in high-focus states where child mortality remains high.